Correlation between measured oral health and oral health-related quality of life in people with epidermolysis bullosa: a prospective cohort study - Theresa Joanning; Guilherme Trento; Jeanette Köppe; Linda Daume; Johannes Kleinheinz; Marcel Hanisch; Ole Oelerich (BMC Oral Health)
Abstract Background Inherited epidermolysis bullosa (EB) is a genetic disorder characterized by skin fragility and unique oral features. This prospective study aimed to analyze the correlation between oral health-related quality of life (OHRQoL) and the objectively measured oral health indices of people suffering from EB and within their subtypes. Methods The German version of the Oral Health Impact Profile (OHIP-14G) was employed for the assessment of OHRQoL. Furthermore, all participants underwent a comprehensive clinical examination to evaluate their oral health via the Physical Oral Health Index (PhOX). Study participants were included through various self-help groups in Germany, regular appointments at the outpatient clinic for rare diseases with orofacial involvement, at the Department of Cranio-maxillofacial Surgery at the University Hospital Münster and through contact via social media. Results A total of 33 individuals participated in the study. The study revealed that both OHRQoL and oral health were reduced. Individuals with dystrophic epidermolysis bullosa (DEB) were more negatively affected than were those in the junctional epidermolysis bullosa (JEB) and epidermolysis simplex (EBS) groups. The OHIP-G14 mean score of participants diagnosed with DEB was 25.2 (95% CI: 18.4–32.0; ± 13.7, range 5–49), and the PhOX mean score of DEB was 54.6 (± 15.7). A significant correlation was observed between PhOX and the OHIP score (rs = -0.54; p < 0.001). Conclusions The findings of this study corroborate the challenges faced by patients with EB in the oral domain and the deterioration of their OHRQoL. These results emphasize the necessity for dentists to engage comprehensively in disease management, encompassing routine examinations, preventive dental care and oral hygiene education. Consequently, enhanced communication is required not only between dental and dermatological teams but also with caregivers.